ANALISIS KELAYAKAN TARIF AIR BERDASARKAN PERATURAN MENTERI DALAM NEGERI NOMER 23 TAHUN 2006 DATA TAHUN 2009 S.D 2012 STUDY KASUS DI PDAM TIRTA DHARMA KABUPATEN SLEMAN - Isna Putri Indayani; Sunarto Sunarto (Jurnal Akuntansi, 2013)
Sleman is Badan Usaha Milik Daerah engaged in water services . Apart from being required to be able to meet the water needs of the customer , PDAM Sleman should be wise in determining water rates are economically viable in order to cover expenses incurred to earn the income . Therefore, analysis of water rates is needed to support revenue growth and taps in accordance with Peraturan Menteri Dalam Negeri Nomor 23 Tahun 2006 article 5 paragraf 1of the PDAM revenues must meet cost recovery principle (full cost recovery ) . In examining the water use rate formula of Peraturan Menteri Dalam Negeri Nomor 23 Tahun 2006 and the data used is the financial statement data PDAM Sleman 2009 till 2012. The calculations show the basic water rates , low rates , and the rates prevailing on the taps full Sleman not meet the principle of full cost recovery. From the results of the study also note that the rate of water from PDAM Sleman 2009 data up to 2012 have not been economically viable because they can not cover the entire cost of business or do not meet the principle of full cost recovery. Keyword: full cost recovery, cost of business, price of water